Factors Related to Oral Health Care Behavior of the Elderly at Sa Saming Sub-District, Warin Chamrap District, Ubon Ratchathani Province - มาลีลัย แก้วใจ; ใจมนต์ จีราพร; นครังสุ ภาณินี; ปานเหลา อัษฎาวุธ; บุญสู่ ถนอมศักดิ์; ปานะบุตร นิลุบล (Journal of Health Science of Thailand, 2022)
This cross-sectional survey study aimed to study the factors associated with and affecting oral health care behaviors of the elderly. It was conducted among active and literate elderly in Sa Saming sub-district, Warin Chamrap District. Ubon Ratchathani Province from December 2018 to February 2019. The sample size was calculated to be 120 people. Data were collected by using a questionnaire that contained general information, knowledge about oral health care, access to oral health care services, social support and oral health care behaviors; and were analyzed using descriptive statistics: frequency distribution, percentage, mean, standard deviation; and inferential statistics: the Pearson correlation coefficient. The results showed that 46.66% of the elderly knew about oral health care (predisposing factors) at a moderate level (mean=0.66, SD=0.48). Most of the elderly (58.33%) had access to oral health care services (enabling factors) at a moderate (mean=1.88, SD=0.76). In addition, 57.50% of them received social support (reinforcing factors) at a low level (mean=1.33, SD=0.55). Most of the active elderly (55.0%) had oral health care behaviors at a moderate level (mean=2.15, SD=0.87). In conclusion, the predisposing factors, enabling factors and reinforcing factors were statistically associated with the oral health care behavior among the active elderly.